Laundry service / Jessey Angat ...[et al.] - Angat, Jessey; Julius Booh, Marysia; Matali, Mohd Farhan; Edih, Putri Edha (Faculty of Applied Sciences, 2009)
Time is precious and Yours Laundry Shop does will help you to solve with your laundry problem. Yours Laundry Shop run professional laundry business dedicated to ensuring you have hassle free laundry days. Due to the good potential on the laundry shop, we as group members have decided to open a laundry called Yours Laundry Shop. Our type of business is a laundry shop which we apply it to all kind of clothes. Before we start the plan to open laundry shop, we have observed the planning area. We believe this industry will develop in the future because of the good potential that we can see from the earlier. Furthermore, the place where we grow the business can develop in the future. Beside, fewer competitors on the area have convinced us to open this laundry shop. We have decided to start this laundry business at Lot 5, Block A, Lorong Plaza Permai 1, Taman Alam Mesra Shoplot, 88400 Kota Kinabalu, Sabah. We choose this place because of its strategic area between the housing areas, the 1 Borneo shopping complex and hotel at the 1 Borneo shopping complex. Our target customer is all kind people, personal or company laundry. The date of commencement for our business is on 1st January 2010. We take a long period of time because we want to identify the best way how to conduct this business and to find the capital for this business. The reason why we involve on this industry is due to some factor. First, laundry shop is not very popular in this region, so we have fewer competitors. We also believe it will make high profit and less capital. Next, laundry shops no need regular maintenance and no need to hire more workers because all work is done by a machine. We only have to buy detergent and softener and maintenance for the laundry machine. Besides, laundry is important to clean a high quantity of clothes. The business potential of this industry is we can expand our business and open our branch at other place. In addition, there is no shortage of people whose wash clothes, because it is one of the basic necessities of life. So, people will seek for the laundry to clean their clothes and other materials, thus can save their time.